2021
DOI: 10.1021/acs.jmedchem.1c01256
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Oxycyclohexyl Acid Lysophosphatidic Acid Receptor 1 (LPA1) Antagonist BMS-986278 for the Treatment of Pulmonary Fibrotic Diseases

Abstract: The oxycyclohexyl acid BMS-986278 (33) is a potent lysophosphatidic acid receptor 1 (LPA1) antagonist, with a human LPA1 K b of 6.9 nM. The structure–activity relationship (SAR) studies starting from the LPA1 antagonist clinical compound BMS-986020 (1), which culminated in the discovery of 33, are discussed. The detailed in vitro and in vivo preclinical pharmacology profiles of 33, as well as its pharmacokinetics/metabolism profile, are described. On the basis of its in vivo efficacy in rodent chronic lung fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Originally, the LPA-induced histamine release was characterized using a LPAR1/3 inhibitor . An acute LPA-induced histamine release assay in mice has been previously used to characterize the pharmaco­kinetic/​pharmaco­dynamic (PK/PD) relationship of different LPAR1 antagonists. …”
Section: Resultsmentioning
confidence: 99%
“…Originally, the LPA-induced histamine release was characterized using a LPAR1/3 inhibitor . An acute LPA-induced histamine release assay in mice has been previously used to characterize the pharmaco­kinetic/​pharmaco­dynamic (PK/PD) relationship of different LPAR1 antagonists. …”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of (S) pyrimidin-4-yl)amino)propyl)piperidin-4-yl)benzenesulfonamide (11). Intermediate 65e (145 mg, 0.27 mmol) was reacted according to the general procedure D. The crude residue was purified by flash chromatography on silica-NH cartridge (eluent: cyclohexane/EtOAc from 100/0 to 40/60) to afford compound 11 (29 mg, 0.06 mmol, 22% yield) as a white solid.…”
Section: Synthesis Of N-((2smentioning
confidence: 99%
“…10 The role of LPA 1 receptors in modulating lung fibrotic processes is well established in the clinic. Bristol Myers Squibb (among others) is studying the LPA 1 receptor antagonist BMS-986278 11 in phase 2 clinical trials for IPF and PF-ILD, while BMS-986020, 12 although discontinued in a phase 2 clinical trial in IPF patients for its hepatobiliary toxicity, showed a statistically significant reduction in the change from baseline of forced vital capacity compared to placebo.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While several LPAR1 antagonists, including BMS-96278, BMS-986020, Ki16425, ONO-730043, and SAR-100842 (Figure ), have been identified to date, their structural similarities, as discussed in a recent review article, highlight the need for expanding the available repertoire of chemical templates capable of inducing LPAR1 antagonism. The importance of this diversification is underscored by BMS-986020’s hepatobiliary toxicity, which was found to be structure-dependent, a contrast to antagonists with distinct structural features that did not exhibit this toxicity .…”
Section: Introductionmentioning
confidence: 99%